The relation of dermcidin with insulin resistance and inflammation in women with polycystic ovary syndrome - Akan,Ozden Yildirim (2022)
SUMMARY OBJECTIVE: Polycystic ovary syndrome is the most common endocrinopathy among women of reproductive age. Polycystic ovary syndrome is a metabolic disorder associated with insulin resistance and subclinical inflammation. Dermcidin, an antimicrobial peptide, involves in insulin resistance and inflammatory processes. Dermcidin suppresses the secretion of insulin production from the liver/pancreas and also increases insulin resistance. We aimed to discover whether dermcidin levels were altered in polycystic ovary syndrome women compared to controls and determine the link of dermcidin with hormonal-metabolic parameters in polycystic ovary syndrome women. METHODS: The current research was designed as a case-control study and Rotterdam 2003 criteria were used for diagnosing polycystic ovary syndrome. A total of 75 subjects with polycystic ovary syndrome and 75 age- and body mass index-matched subjects as controls were enrolled in the study. The insulin resistance state was determined using a homeostatic model assessment of insulin resistance and quantitative insulin sensitivity check index. High-sensitivity C-reactive protein levels were assessed to define inflammation. RESULTS: Circulating dermcidin levels were measured by enzyme-linked immunosorbent assay. Dermcidin levels were significantly increased in polycystic ovary syndrome subjects compared to controls (172.53±42.41 ng/mL vs. 108.44±31.69 ng/mL, p<0.001). Homeostatic model assessment of insulin resistance and high-sensitivity C-reactive protein levels were markedly increased, whereas quantitative insulin sensitivity check index levels were notably decreased in women with polycystic ovary syndrome compared to controls. Linear regression analysis revealed that dermcidin exhibited an independent link with homeostatic model assessment of insulin resistance and high-sensitivity C-reactive protein, whereas dermcidin displayed an inversely independent link with quantitative insulin sensitivity check index. CONCLUSION: Increased dermcidin levels were associated with insulin resistance and inflammation in polycystic ovary syndrome women, suggesting that dermcidin may play a role in the pathophysiology of polycystic ovary syndrome.